2019
DOI: 10.48084/etasr.3094
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Battery Sizing of a Grid-Connected Residential Photovoltaic System for Cost Minimization using PSO Algorithm

Abstract: This paper proposes a new optimization technique that uses Particle Swarm Optimization (PSO) in residential grid-connected photovoltaic systems. The optimization technique targets the sizing of the battery storage system. With the liberation of power systems, the residential grid-connected photovoltaic system can supply power to the grid during peak hours or charge the battery during non-peak hours for later domestic use or for selling back to the grid during peak hours. However, this can only be achieved when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The functional structure design of the personalized distance education learning management system is based on the use case model and participant model of demand analysis. It divides the system into modules such as system management, information release management, teaching resource management, auxiliary management, and personalized learning management [ 25 ]. The specific functional structure is shown in Figure 10 .…”
Section: Design and Analysis Of The Intelligent Education Personalize...mentioning
confidence: 99%
“…The functional structure design of the personalized distance education learning management system is based on the use case model and participant model of demand analysis. It divides the system into modules such as system management, information release management, teaching resource management, auxiliary management, and personalized learning management [ 25 ]. The specific functional structure is shown in Figure 10 .…”
Section: Design and Analysis Of The Intelligent Education Personalize...mentioning
confidence: 99%
“…The authors concluded that deferral benefit depends on upgrade timing. Authors in [16] applied the Particle Swarm Optimization (PSO) algorithm to optimally size lead acid BESS in a grid-connected residential photovoltaic system for cost minimization. The NPV method was followed to evaluate the investment deferral value of microgeneration in EHV DNs in [17] wherein the benefit was depending on microgeneration placement.…”
Section: Introductionmentioning
confidence: 99%
“…In general, induction motors have the potential advantages of low cost and a wide speed range but are less efficient than Permanent Magnet Synchronous Motors (PMSM) despite the use of the loss minimization algorithm [1]. In [1][2][3][4][5][6][7][8][9][10][11][12][13][14], a wide range of mathematical and soft computing methods were addressed. In [1], a mathematical loss minimization algorithm was developed to minimize the power loss of PMSM and balance the EV energy.…”
Section: Introductionmentioning
confidence: 99%